ANALISIS PENGUKURAN KINERJA MENGGUNAKAN BALANCED SCORECARD DENGAN METODE OMAX DAN TRAFFIC LIGHT SYSTEM PADA PT ATP - Sugijono, Latricia Kylene; Ahmad; Saryatmo, M Agung (Universitas Tarumanagara, 2024)
PT ATP is a company operating in the field of construction materials and services. So far, PT ATP has not fully carried out performance calculations. the company's performance assessment only focuses on the financial sector. This measurement causes the company's orientation to only focus on short-term profits. Therefore, companies need to carry out analysis and identify overall company performance measurements to find out the causes of existing problems. This research will be conducted using the Balanced Scorecard (BSC) method. Primary data used in this research was obtained from observations, interviews and discussions with the company as well as by filling out questionnaires with the company. Secondary data such as company revenue data, sales data, customer number data comes from data that the company has had for the last 6 years. Based on the results of performance measurements using OMAX, it is known that the overall results of the company's performance have a weight of 5.118, indicating that the company's performance is sufficient but has not reached the target and still requires improvement. The results of calculations using the Objective Matrix (OMAX) and Traffic Light System (TLS), it is known that there are 3 green indicators whose performance is good, 5 yellow indicators whose performance is sufficient but still below the target, and 4 red indicators whose performance is still far below target.